A method for the calculation of Detectable Landslide using Terrestrial Laser Scanning data. (August 2020) - Chen, Xijiang; Ban, Ya; Hua, Xianghong; Lu, Tieding; Tao, Wuyong; An, Qing
Highlights: The original and actual Point cloud error ellipsoid is obtained. The point error entropy of n-dimensional P-norm distribution is obtained. We give the entropy error ellipsoid. MDL is determined according to the semi-principal axes of entropy error ellipsoid. Abstract: Terrestrial laser scanning (TLS) has been widely used in various fields, especially it is relatively new, versatile, and efficient technology for landslide monitoring. The landslides are always obtained by comparing point cloud over the same area. But, whether the comparing value comes from landslide or point cloud error is not determined. Hence, it is vital to analyze the point cloud error, and to determine the magnitude of detectable landslide (MDL), and further estimate the real landslide region according to the difference of comparing. In this paper, the error entropy was used to construct the point cloud error entropy according to the relation between adjacent point error entropy, and further to determine the MDL. The simulated landslide point clouds were used to evaluate the performance of the proposed method. This proposed method was applied to landslide monitoring located at Jinduicheng Open Pit Mine. The results show that the Detectable landslide regions are determined according to MDL.